2004
DOI: 10.1242/dev.01133
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the forebrain: FoxA4a/Pintallavis and Xvent2 determine the posterior limit ofXanf1expression in the neural plate

Abstract: During early development of the nervous system in vertebrates, expression of the homeobox gene Anf/Hesx1/Rpx is restricted to the anterior neural plate subdomain corresponding to the presumptive forebrain. This expression is essential for normal forebrain development and ectopic expression of Xenopus Anf, Xanf1 (also known as Xanf-1),results in severe forebrain abnormalities. By use of transgenic embryos and a novel bi-colour reporter technique, we have identified a cis-regulatory element responsible for trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…The XlFgf8a cDNA was obtained by PCR with the following primers: forward 5Ј-AGAATTC-CCACCATGAACTACATCACCTCC; reverse 5Ј-ACTCGAGTTACCGA-GAACTTGAATATC. The VP16-Xanf1-BDG, EnR-Xanf1-BDGR, Otx2, Otx2-BDGR and Noggin constructs have been described previously (Ermakova et al, 1999;Martynova et al, 2004;Lamb et al, 1993). Capped mRNAs for microinjections were synthesized by mMESSAGE mMACHINE kit (Ambion).…”
Section: Preparation Of Dna Constructs Synthesis and Injections Of Mmentioning
confidence: 99%
“…The XlFgf8a cDNA was obtained by PCR with the following primers: forward 5Ј-AGAATTC-CCACCATGAACTACATCACCTCC; reverse 5Ј-ACTCGAGTTACCGA-GAACTTGAATATC. The VP16-Xanf1-BDG, EnR-Xanf1-BDGR, Otx2, Otx2-BDGR and Noggin constructs have been described previously (Ermakova et al, 1999;Martynova et al, 2004;Lamb et al, 1993). Capped mRNAs for microinjections were synthesized by mMESSAGE mMACHINE kit (Ambion).…”
Section: Preparation Of Dna Constructs Synthesis and Injections Of Mmentioning
confidence: 99%
“…By ectopic expression it was found to induce the floor plate marker F-spondin (Ruiz i Altaba et al, 1993a). Shortly after, FoxA4 was shown to synergistically induce mesodermal derivatives in combination with Xbra (O'Reilly et al, 1995) and, as already mentioned, FoxA4 was recently shown to be involved in the patterning of the forebrain (Martynova et al, 2004). Interestingly, for both FoxA2 and FoxA4, an interplay with homeodomain proteins has been described.…”
Section: Functionmentioning
confidence: 93%
“…Besides Mix.2, which was shown to be directly regulated by FoxH1a and H1b (Chen et al, 1996;Howell et al, 2002), FoxA4a was recently found to bind directly and to repress together with Xvent-2 the Xanf1 promoter, thus restricting the expression area of Xanf1 to the anterior neural plate (Martynova et al, 2004). This is of special interest because up to now, all members of the FoxA subclass were thought to function as activators (e.g., reviewed in Kaestner, 2000).…”
Section: Functionmentioning
confidence: 99%
“…The mRNA was found along the edge of the neural tube [3,5,6,9] along the edge of the presumptive forebrain [13], in the presumptive eyes, bronchial arch, tail bud [3][4][5][6] somites [3] and in the areas of the mieloid ventral blood island [4,5,25]. The Xvent-2 mRNA was absent in the cement gland [3][4][5][6].…”
Section: Spatial Patterning Of the Xvent-2 Protein Inmentioning
confidence: 99%
“…The presence of the homeodomain and its specific sequence certificate this protein to be a transcription factor of a BarH subfamily. This gene is a target of the BMP signaling pathway in Xenopus and plays an important role in the dorsoventral patterning in amphibia and fish [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%